Tectonic perspectives for urban ambiance? Towards a tectonic approach to urban design - Elias Melvin Christiansen; Lea Holst Laursen; Marie Frier Hvejsel (Ambiances)
Urban challenges derived from climate prospects and densification call for a renewed engagement with the question of the liveability of the built environment. Within this context, the economic and technical concept of our cities is an increasingly dominant aspect, whereas the fragile but vital question of ambiance that seemingly signifies our sense of liveability is often suppressed. This requires us, as architects and urban designers, to refine our descriptions of ambiance as an integral part of the technical construction principles applied in the built environment, hereby considering it a continuous space, as suggested in theories of landscape urbanism. By recalling the etymological meaning of tectonics as a contextual joining of aesthetics and technology at the architectural scale, the paper states that this can be understood as a tectonic challenge which crosses the architectural and urban domains. As a result, the potential is opened up to develop further the theory of landscape urbanism by juxtaposing it with tectonic architectural theory. The paper investigates this potential through a combined conceptual and analytical case, studying whether it is possible to define and describe urban ambiances across scale, in relation to the concept of the built environment, when applying an “urban tectonic” perspective.